The reasons for the failure of Bishara CO2 compressor belonging to Southern Fertilizer Company (Baghdad Science Journal, 2006)
In this research study failed Annunciation No. 10 for the fourth phase of the pressure of carbon dioxide of the company for Southern Fertilizers and repeated the failures more than once for the same gospel was a detailed study of the gospel included a series tests for properties Mechanical and Structural addition to the tests microscopic and scanning electron microscope shows m This study parameters and a failure Elal well as the existence of an old internal cracks in the metal of the Annunciation